Adjunctive use of fluoroscopy during MitraClip implantation reduces procedural complexity: The parallax technique. Issue 4 (12th October 2020) - Singh, Gagan D.; Rogers, Jason H; Chen, Sarah; Yap, Jonathan; Smith, Thomas W.R.; Fan, Dali; Stripe, Benjamin; Aman, Edris
Abstract: Background: During MitraClip implantation sub‐valvular correction of trajectory and/or alignment may increase adverse clip or leaflet events. With systematic adjunctive use of fluoroscopy (" Parallax technique "), we aimed to assess parameters that minimize the need for corrective measures and help increase procedural efficiency. Methods: We retrospectively analyzed 30 patients without (Fl‐) and 39 patients utilizing adjunctive fluoroscopy (Fl+) during MitraClip implantation. After establishing trajectory and supra‐valvular alignment, the Parallax technique was utilized. Trajectory and alignment are maintained during advancement. Results: All patients had 3 or 4+ MR. There were no differences in baseline demographics. The average number of clips (Fl‐ vs Fl+) was 1.72 ± 0.8 vs 1.59 ± 0.5, p = .57. For the first clip, the need for sub‐valvular alignment (80% vs. 36%, p = .0001), eversion with retraction back to left atrium (23% vs. 10%, p = .001) and the number of grasps (2.3 ± 1.2 vs 1.4 ± 0.9) was reduced. The time from transseptal puncture to first clip deployment (71 ± 21 vs 44 ± 16 min, p = .01) was reduced. Procedural success was achieved in all but one patient in the Fl‐ group (p = ns). There were no differences noted for in‐hospital or 30‐day outcomes. Conclusions: Systematic use of a simple and easy to implement "Parallax technique" was associated with reduced need for sub‐valvular manipulation and was associated with improved procedural times. Further larger scale studies are needed to assess the applicability of the technique.